Analysis of Operational Costs and Amount of Musi Emas LRT Feeder Transportation Rates in Palembang - Effendi*, Andriani; Agustien, Melawaty; Kadarsah, Edi (Riwayat: Educational Journal of History and Humanities, 2023)
This research aims to analyze operational costs and assess the feeder transportation rates for the Musi Emas LRT in Palembang. The research methods used include field surveys and data analysis. The research results show that the average load factor for the Talang Kelapa-Talang Buruk and Haji-Sematang Borang Dormitory routes is 0.40, indicating that the available seating capacity (9 seats) is currently adequate. The number of passengers per day is 1,183 for the Talang Kelapa-Talang Buruk Route and 987 for the Haji-Sematang Borang Dormitory, with a total fleet of 26 units, and 6 routes per day per vehicle. The travel time for the Talang Kelapa-Talang Buruk route is 1.5 hours and the Haji-Sematang Borang Dormitory is 2 hours. The time between stops varies, namely the Talang Kelapa-Talang Buruk route is around 15 minutes, while the Haji-Sematang Borang Dormitory is around 20 minutes. This is not in accordance with the standards of the Director General's Decree 687 of 2002, resulting in too long waiting times for passengers. The conclusion of this research is that the feeder transportation rates for the Musi Emas LRT on the Talang Kelapa-Talang Buruk Route and the Haji-Sematang Borang Dormitory need to be adjusted to the standard operational costs and time between stops which have been standardized by the Director General's Decree 687 of 2002 to minimize passenger waiting time and ensure the continuity of efficient and economical operations.